COMPUTATIONAL STUDY OF ANTIOXIDANT, TOXICITY, DRUG SCORING AND MOLECULAR DOCKING OF THE STRUCTURE OF CATECINS - Anggriany, Martania; Adlis Santoni; Emriadi; Imelda (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Chronic disorders such as cancer can be caused by an imbalance in free radical production with antioxidant defenses in the body. This research aims to obtain the best compounds as future drug candidates. The potential of catechin compounds and their derivatives as cancer drug candidates has been studied through antioxidant properties, toxicity, drug scores and molecular docking. In this research, antioxidant activity was studied using the DFT (Density Functional Theory)/B3LYP/3-31G method in the gas phase. Toxicity and drug scores were analyzed using OSIRIS Property Explorer software. Analysis of the interaction of catechin and modified catechin compounds with 5KYK cell protein using MOE (Molecular Operating Environment) software. The research results show that the antioxidant properties are well explained through the antioxidant reaction mechanism which occurs more easily in the Single Electron Transfer – Proton Transfer (SET – PT) mechanism. The total energy produced by IP (Ionization Potential) + PDE (Proton Dissociation Enthalphy) is smaller. Catechin compounds and their derivatives are not toxic (no risk) for gene mutations, tumors, irritation and reproduction. Catechin compounds and modified catechins (1-5) have a drug score value of (0.453-0.871). It is estimated that catechin compounds and their derivatives can be used as potential antioxidants without side effects on biological systems. From the pharmacophore study, it was found that the compound that had the best interaction with the 5KYK receptor was compound 1.